Development of Alternative Projectile to Deactivate an Improvised Explosive Device – Pipe Bomb - Lichorobiec, Stanislav (Communications - Scientific letters of the University of Zilina, 2011)
The article describes a possibility of dealing with the problem represented by an improvised explosive device in the form of a pipe bomb so that the problem may be solved quickly and reliably, i.e. so that the pipe bomb may be deactivated without explosion. The article describes the development of an alternative projectile that will replace the water content in the water gun; thus it will make it possible to remove metallic end caps closing pipe bombs so that the bombs can be disassembled without explosion, and subsequently to subject the dismantled parts to forensic examination to detect a designer of the improvised pipe bomb.